Comparative Effect of Niel-Asher Technique and Positional Release Technique on Pain, Active ROM and Functional Disability in Adhesive Capsulitis: An Experimental Study - Raghav, Deepak; Krishnapandian, Prabhu Ram; Dwivedi, Amit (Journal of clinical and diagnostic research, 2023)
Introduction: Adhesive Capsulitis of Shoulder (ACS) is a common self-limiting disorder characterised by painful, progressive loss of active and passive shoulder motion due to fibrosis and rigidity of the joint capsule. ACS occurs in 2-5% of the population overall and up to 20% of those with diabetes. Women between the ages of 40 and 60 are at increased risk, and one in four patients may have bilateral illness. Several studies have been done to prove the effectiveness of electrotherapeutic modalities and manual mobilisation techniques on Adhesive Capsulitis, but very few studies have been done to find out and compare the effectiveness of Niel-Asher technique and Positional Release Technique (PRT) on adhesive capsulitis. Aim: To compare effect of Niel-Asher technique and positional release technique on pain, active Range of Motion (ROM) and functional disability in patients with adhesive capsulitis. Materials and Methods: This was a pre and post-experimental design conducted at Santosh Medical College and Hospital, Ghaziabad, India, for a duration of two years conducted on 110 patients with a diagnosis of stage II primary adhesive capsulitis. The patients were divided into group A and group B using a systematic random sampling procedure. Conventional physiotherapy and the Niel-Asher technique were used on patients in group A. Patients in group B received conventional physiotherapy and Positional Release Technique. The therapy was given to patients, three times weekly for a total of six weeks. The Shoulder Pain and Disability Index (SPADI), Range of Motion (ROM) and Visual Analogue Scale (VAS) were measured in both groups in pre, mid and post-therapy. The analysis of the collected data was done by Statistical Package for Social Sciences (SPSS) software version 17.0. Results: A total of 110 patients with adhesive capsulitis patients, 55 in each group A (mean age: 51.78±7.810 years) and group B (mean age: 52.33±7.794 years) were included in the study and the mean age of total study subjects was 52.05±7.80 years. On analysis of the collected data, statistically significant outcomes across all three measures (VAS, SPADI, and ROM) were observed with a p-value of less than 0.001. In pain, functional impairment and restricted ROM, group A, outperformed group B in this comparison. Conclusion: Both conventional physiotherapy along with NielAsher technique group and conventional physiotherapy along with PRT group were individually effective in relieving pain and improving Range of Motion and Functional ability in patients with Adhesive capsulitis, but among these two groups, the group that received Niel-Asher technique in addition to conventional physiotherapy reported more significant improvements when compared to PRT group, in pain, range of motion and functional ability.